Perbandingan Performansi Protokol Routing pada Jaringan Mobile Ad Hoc Network - Pratama, Andi; Maulana, Rizky; Lestari, Dewi (Journal of Computer Science and Information Technology, 2026)
Mobile Ad Hoc Networks (MANETs) rely on dynamic routing mechanisms due to their infrastructureless and highly mobile nature. Selecting an appropriate routing protocol remains a critical issue because network performance is influenced by node mobility, density, and traffic conditions. This study aims to comparatively analyze the performance of major MANET routing protocols, including AODV, DSDV, OLSR, DSR, and related variants, based on findings from prior simulation and experimental studies. A systematic literature-based comparative method was employed by synthesizing performance metrics such as packet delivery ratio, throughput, end-to-end delay, routing overhead, and energy consumption from multiple NS2/NS3 and OPNET-based research works. Results show that AODV consistently performs well in dynamic and large-scale networks, offering high packet delivery and moderate delay, while OLSR excels in dense topologies but generates higher overhead. DSDV demonstrates stability in low-mobility environments, whereas DSR shows efficiency in smaller networks. The study concludes that no single protocol is universally optimal; protocol selection should align with network scale, mobility, and application requirements. This research provides a consolidated reference to support adaptive MANET routing protocol selection.